1987
DOI: 10.1148/radiology.163.3.3575731
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal sinuses: CT imaging requirements for endoscopic surgery.

Abstract: Recent advances in the understanding of mucociliary activity and the pathophysiology of the nasal cavity and paranasal sinuses have revolutionized the surgical management of chronic and/or recurrent sinusitis. Meticulous radiographic delineation of the small structures in this region, coupled with endoscopic evaluation, provides detailed preoperative information regarding morphology and pathology. This information has led to more focused endoscopic surgical procedures, which have dramatically reduced patient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
155
1
15

Year Published

1988
1988
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(189 citation statements)
references
References 4 publications
12
155
1
15
Order By: Relevance
“…This residual disease could spread and lead to persistence of Sagittal reconstructions were life-size to allow direct measurements on scan to judge depth of ethmoidal or sphenoidal sinuses from inferior nasal spine. [5,6]. If diseased tissue in the ethmoidal area and common drainage site in the middle meatus is removed by endoscopic surgery and mucociliamy clearance and ventilation are returned to normal, the maxillary and frontal sinuses also may clear [4].…”
Section: Discussionmentioning
confidence: 99%
“…This residual disease could spread and lead to persistence of Sagittal reconstructions were life-size to allow direct measurements on scan to judge depth of ethmoidal or sphenoidal sinuses from inferior nasal spine. [5,6]. If diseased tissue in the ethmoidal area and common drainage site in the middle meatus is removed by endoscopic surgery and mucociliamy clearance and ventilation are returned to normal, the maxillary and frontal sinuses also may clear [4].…”
Section: Discussionmentioning
confidence: 99%
“…Zinreich et al, [33] and Kennedy et al, [34] described Haller's cells as ethmoid air cells found inferior to the ethmoid bulla adhering to the roof of the maxillary sinus, in continuity with the proximal infundibulum, which formed part of the lateral wall of the infundibulum [Table/ Fig-6]. They are considered as ethmoid cells that grow into the floor of orbit and may narrow the adjacent ostium of the maxillary sinus especially if they become infected [35].…”
Section: Haller's Cellmentioning
confidence: 99%
“…1 Functional endoscopic sinus surgery (FESS) addresses these anatomical variations and mucosal diseases and restores the normal physiology of the paranasal sinuses. 2 Preoperative evaluation of these variants is also important being a part of surgical safety. 3 Diagnostic nasal endoscopy and computed tomography play a vital role in accurate assessment of anatomical variations.…”
Section: Introductionmentioning
confidence: 99%